Pelatihan Aplikasi WARP PLS Dan Aplikasi Mendeley Untuk Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Agustinus Salle; Klara Wonar (The Community Engagement Journal, 2020)
The training discusses WarpPLS 5.0, which can be used on the structural model of reflective or formative indicators models. WarpPLS 5.0 It also provides variable moderation and mediation testing (even three segments) more simply. In addition, it also provides a relationship analysis between latent variables that are not linear. The training focuses on the application (applied philosophy) of the WarpPLS method & the operating skills of Software WarpPLS-5.0, as well as avoiding complicated and complex discussions of mathematics and statistics. Meanwhile, Mendeley training, which aims at the management of citation and literature in student scientific work, can increase students ' understanding of their operation in supporting the quality of citation and reference of student's scientific work.